Breaking barriers in STEAM education: Analyzing competence acquisition through project-based learning in a European context - Paula García-Llamas; Angela Taboada; Patricia Sanz-Chumillas; Luísa Lopes Pereira; Roberto Baelo Álvarez (International Journal of Educational Research Open)
Project-Based Learning (PBL) is a widely applied methodology to foster professional competencies, especially when integrated with STEAM education. This study assesses the impact of a STEAM PBL activity on higher education students and academics, regarding competence acquisition (i.e., personal, professional, academic, and social competences). Additionally, it explores how participants' profiles and learning backgrounds shape their perceptions of PBL benefits by analyzing their motivations, expectations, and attitudes toward the methodology. Participants included higher education students and academics from six universities across five European countries. Data was collected through questionnaires across four domains: expectations and motivation, self-perception, competence acquisition, and satisfaction. Responses were analyzed using GLM to evaluate the influence of gender and academic role, and program modality (national or international) on participants' perceptions. Results show that both students and academics perceived similar benefits from PBL, regardless of their background or study modality. They reported high satisfaction and significant competency acquisition across all areas, with no significant differences based on gender, academic role, or prior experience, which highlights PBL as an inclusive methodology for diverse participants’ profiles. The primary motivation for participation was to gain practical skills and engage in international collaboration, with minimal influence from external rewards. The findings stress the effectiveness of the PBL approach in STEAM education for fostering key competencies in higher education, promoting personal and professional growth, collaboration, and practical application of STEAM disciplines. The inclusiveness and effectiveness of PBL for diverse profiles supports its broader implementation in STEAM education to better prepare students for global challenges.